Attachment‐Related Representations and Suicidal Ideations in Nonsuicidal Self‐Injury Adolescents with and without Suicide Attempts: A Pilot Study. Issue 4 (16th March 2020) - Pallini, Susanna; Terrinoni, Arianna; Iannello, Sara; Cerutti, Rita; Ferrara, Mauro; Fantini, Fiorella; Laghi, Fiorenzo
Abstract : Objectives: Consistent with the debate surrounding the association between nonsuicidal self‐injury (NSSI), suicidal intent, and suicidal behavior, and between NSSI and dysregulation processes, we attempted to analyze suicide intent and emotion dysregulation in NSSI adolescents, in the framework of the attachment representations and exploring these clues of emotion dysregulation characteristics of insecure attachment. Furthermore, we intended to focus on these attachment‐related segregated systems regarding death and suicidal ideations, to explore how differently they would characterize self‐injuring adolescents with and without suicide attempts. Methods: Thirty‐four NSSI inpatient adolescents, 17 with suicide attempts, 17 without suicide attempts, and 17 healthy controls (age 11–17) were assessed using Adult Attachment Projective, which allows for the classification of attachment status and related emotion dysregulation and segregated systems. Results: The majority of the NSSI group with and without suicide attempts showed unresolved (disorganized) attachment‐related representations and clues of damaged reflective functions, whereas only the NSSI with suicide attempts showed clues of impaired interpersonal relationships. The two clinical groups used words expressing suicidal intent, whereas the healthy group did not. Conclusions: Therapists are encouraged not to underestimate suicidal ideation in NSSI regardless of whether or not they have already attempted suicide.